Management of technology : managing effectively in technology-intensive organizations - Thamhain, Hans J. 1936- (John Wiley, 2005)
* Presents assessment methods for organization and management processes. * Provides special tools and techniques for managing and organizing R & D, new product, and project-oriented challenges. * Includes real-world case studies.